Body height in adult women and men in a cross-sectional population-based survey in Geneva: temporal trends, association with general health status and height loss after age 50 - Silvia Stringhini; Idris Guessous; Kaspar Staub; Julia Schäppi; Katarina L Matthes (BMJ Open)
Objective On the one hand, trends in average height in adulthood mirror changes in living standard and health status of a population and its subgroups; on the other hand, height in general, as well as the loss of height in older age in particular, are associated in different ways with outcomes for health. For these aspects, there is hardly any information for Switzerland based on representative and measured body height data.Design Repeated cross-sectional survey study.Setting Fully anonymised data from the representative population-based Geneva Bus Santé Study between 2005 and 2017 were analysed.Methods Data from N=8686 study participants were used in the trend analysis. Height was measured and sociodemographic information and self-rated health was collected via questionnaires. Follow-up (mean: 7.1 years) measurements from N=2112 participants were available to assess height loss after age 50.Results Women were, on average, 166.2 cm (SD 6.5) tall and men 179.2 cm (SD 6.5). Among men and women, higher socioeconomic status was associated with taller average height. The flattening of the increase in height from the 1970s birth years appears to begin earlier in the subgroup with the highest education level. The tallest average height was measured for men and women from Central and Northern Europe, the shortest for South America and Asia. The likelihood that participants rated their health as ‘very good’ increased with greater body height. The follow-up data show that men lost −0.11 cm per follow-up year (95% CI −0.12 to −0.10), women −0.17 cm (95% CI −0.18 to 0.15).Conclusions The association of height and health status is currently understudied. Monitoring changes in average body height may indicate disparities in different subgroups of populations. Based on our study and a growing literature, we think that the multifaceted role of body height should be better considered in clinical practice.